Review of Lula and his politics of cunning: From metalworker to president of Brazil - Kat, Quintijn B. (European Review of Latin American and Caribbean Studies, 2022)
Lula and his politics of cunning: From metalworker to president of Brazil, John D. French. University of North Carolina Press, 2020